1991
DOI: 10.1111/j.1365-2958.1991.tb01845.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of a rare codon specifically during development?

Abstract: Summary A range of circumstantial evidence suggests that in Streptomyces spp., genes required for vegetative growth do not contain the leucine codon TTA. Instead, the codon seems to be confined to a few genes necessary during differentiation, when the colonies begin to produce aerial hyphae and antibiotics. Thus, mutations in bldA, the structural gene for tRNALeuTTA, do not retard vegetative growth, but they prevent normal aerial mycelium and antibiotic production. Most of the known TTA‐containing genes specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
79
0
2

Year Published

1992
1992
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(81 citation statements)
references
References 36 publications
0
79
0
2
Order By: Relevance
“…Sure enough, the sequence showed that bldA could not encode a protein but rather would produce a typical tRNA with the anti-codon UUA ( TTA in DNA) (Lawlor et al, 1987). So was born the concept of a developmental switch that is dependent on the absence of the rare TTA codon for leucine from all genes required for vegetative growth, but present in a limited number of genes expressed post-exponentially (Leskiw et al, 1991). This idea was strikingly illustrated by the finding of a TTA codon in the 5h region of actII-ORF4, the gene for the pathway-specific activator of the actinorhodin cluster : mutation of this codon to TGA restored antibiotic production in a bldA background (Ferna!…”
Section: The In Silico Yearsmentioning
confidence: 99%
“…Sure enough, the sequence showed that bldA could not encode a protein but rather would produce a typical tRNA with the anti-codon UUA ( TTA in DNA) (Lawlor et al, 1987). So was born the concept of a developmental switch that is dependent on the absence of the rare TTA codon for leucine from all genes required for vegetative growth, but present in a limited number of genes expressed post-exponentially (Leskiw et al, 1991). This idea was strikingly illustrated by the finding of a TTA codon in the 5h region of actII-ORF4, the gene for the pathway-specific activator of the actinorhodin cluster : mutation of this codon to TGA restored antibiotic production in a bldA background (Ferna!…”
Section: The In Silico Yearsmentioning
confidence: 99%
“…bldA mutations (including deletions) did not interfere with vegetative growth but did prevent aerial mycelium formation and antibiotic production (see [18] for a review). It was suggested that this rare codon occurred preferentially in genes concerned with differentiation and antibiotic production as contrasted with those required for vegetative growth.…”
Section: Streptomycesmentioning
confidence: 99%
“…The fact that although bidA4 point mutations prevent the formation of normal aerial hyphae and block antibiotic production, they have no apparent effect on vegetative growth of S. coelicolor led to the prediction that genes needed for primary growth of S. coelicolor should be devoid of TTA codons. Indeed, when the sequences of 100 known Streptomyces genes were scanned, the occurrence of TTA codons was shown to be nonrandom with respect to the class of genes concerned (36). Most of the TTA-containing genes specify antibiotic-resistance proteins or antibiotic-pathwayspecific regulators associated with the production of antibiotics, including actinorhodin (15), bialaphos (40), streptomycin (14), and spiramycin (19).…”
mentioning
confidence: 99%
“…A few lincomycin-resistant transformants, potentially resulting from a double-crossover event (Fig. 1A) At 15,18,24,30,36,42,48, and 54 h after incubation, samples of the cultures were collected in duplicate, and cell extracts were prepared as previously described (18), except that lysozyme was not used. The final resuspension volume varied from 0.25 to 1.0 ml, depending on the culture density.…”
mentioning
confidence: 99%